Standard Operating Procedure for the Arrests and Detentions of Individuals with Autism in Four Countries - Mohd Kusrin, Zuliza; Ab Rahman, Roseliza Murni; Samuri, Mohd Al Adib; Muhd Adnan, Nurul Ilyana (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Autism spectrum disorder (ASD) is categorized under neuro-developmental disorders. Individuals with this disorder experience deficits in social interaction and communication skills as well as repetitive patterns of thoughts and behaviours. The purpose of this study was to comparatively analyze the similarities and differences in Malaysian PDRM Autism SOPs with other countries, namely Malaysia, Hong Kong, the United Kingdom, and four countries in the United States, namely, Wisconsin, New Mexico, Illinois, and Virginia. This research focuses on discussing the important elements emphasized in SOPs and some aspects of similarities and differences between them. The research design is based on document analysis. The data were analyzed descriptively and thematically. Research results that autistic people put them at risk of committing violations of the law without realizing or intending to do so. Since they are also categorized as persons with disabilities, they are thus entitled to legal guarantees appropriate to their status. Therefore, their rights to equality and non-discrimination as persons with disabilities attracted worldwide attention holistically, resulting in specific Standard Operating Procedures (SOPs) in several countries, including Malaysia, namely, the Royal Malaysian Police Autism SOP (PDRM). Likewise, there are several important elements outlined in all SOPs, in aspects of their application, legal references, methods of arrest and detention, and intermediary assistance, and there are some similarities and differences between the SOPs analyzed. The implications of this study show the importance of SOPs for autism arrest and prisoners, to meet their specific legal needs.